Primer registro de periconia atropurpurea (Berk. Curt.) litvinov en el cultivo del arroz (Oryza sativa L.) - Sandoval Ramirez, I.=700 1 Estrada Vilardell, G.
(Es, En)
Ilus., 5 ref.
Keywords: ORYZA SATIVA; PERICONIA; ENFERMEDADES FUNGOSAS; ESPECIES NUEVAS; REGISTRO; CUBA; PERICONIA ATROPURPUREA